1993
DOI: 10.1111/j.1365-2117.1993.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric flexure as a control on stratal geometry and fades distribution in Upper Cretaceous rocks of the Alberta foreland basin

Abstract: Facies distributions, stratal geometry and regional erosional bevelling surfaces in Upper Cretaceous (Cenomanian‐Santonian) strata of the Alberta foreland basin are interpreted in terms of high‐frequency (probably eustatic) relative changes in sea level, superimposed on longer‐term basin‐floor warping, related to episodic tectonic loading. Thick marine shales correspond to periods of rapid subsidence whereas thin but extensive strandplain sandstones record rapid progradation during slow subsidence. Westward‐th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 8 publications
3
50
0
Order By: Relevance
“…As documented in a series of case studies in the Western Interior foredeep of Canada and the United States (e.g., Hart and Plint, 1993;Plint et al, 1993;Pang and Nummedal, 1995;Donaldson et al, 1998), flexure over reactivated crustal faults resulted in varying rates of subsidence across basement block boundaries, explaining localized incision, paleogeographic trends, and thickness and facies patterns that parallel terrane boundaries in the basement. The importance of basement tectonics on sedimentation was challenged by Aitken (1993), who noted that many basement features are only occasionally reflected, if at all, in the sedimentary cover overlying the basement.…”
Section: Additional Controlsmentioning
confidence: 95%
“…As documented in a series of case studies in the Western Interior foredeep of Canada and the United States (e.g., Hart and Plint, 1993;Plint et al, 1993;Pang and Nummedal, 1995;Donaldson et al, 1998), flexure over reactivated crustal faults resulted in varying rates of subsidence across basement block boundaries, explaining localized incision, paleogeographic trends, and thickness and facies patterns that parallel terrane boundaries in the basement. The importance of basement tectonics on sedimentation was challenged by Aitken (1993), who noted that many basement features are only occasionally reflected, if at all, in the sedimentary cover overlying the basement.…”
Section: Additional Controlsmentioning
confidence: 95%
“…However, Ross and Eaton (1999) suggested that there is little direct relationship between the Precambrian basement and presence and orientation of faults in the sedimentary section in the Alberta basin. In addition, in an earlier study by Plint et al (1993) it was suggested that at the British Columbia-Alberta border a forebulge zone controlled deposition of the Doe Creek and Pouce Coupe sandstones. Therefore, we interpret the hinge zone as a migratory forebulge (Fig.…”
Section: Late Cenomanianmentioning
confidence: 96%
“…18B). This situation probably mainly reflects the gradual sea-level rise, although early phases of the forebulge retreat might also play a role (Plint et al, 1993;Lesczyński & Nemec 2014). The interplay between sediment supply, basement relief, eustatic sea-level changes, and tectonics affected the frequent bathymetric changes and shoreline trajectory (dynamic stratigraphy of foredeep peripheral unconformity -see Lesczyński & Nemec 2014).…”
Section: Discussionmentioning
confidence: 99%